Parkinson's Disease: Impulsivity Does Not Cause Impulse Control Disorders but Boosts Their Severity - Marín-Lahoz, Juan; Pagonabarraga, Javier; Martinez-Horta, Saul; Fernandez de Bobadilla, Ramón; Pascual-Sedano, Berta; Pérez-Pérez, Jesús; Gironell, Alexandre; Kulisevsky, Jaime (Frontiers in Psychiatry, 2018)
Introduction: Impulse control disorders (ICDs) are a common complication of Parkinson’s disease (PD) receiving dopamine agonist (DAA) Impulsivity is considered an underlying mechanism but evidence of this relationship is scarce. To explore the relationship between impulsivity and the presence and severity of ICD in PD. Methods: Prospective cross-sectional study of consecutive PD outpatients. Patients with dementia or previously known ICDs were excluded. Two measures of impulsivity were assessed: Barratt Impulsiveness Scale (BIS-11) for impulsiveness trait (main exposure) and commission errors in the Continuous Performance Test (CE) for motor inhibition. Main outcomes were diagnosis of ICD based on a comprehensive clinical interview and severity of ICD based on the Questionnaire for Impulsive-Compulsive Disorders. Results: Of 100 patients (mean [SD] age, 67.2 [8.8], 54 male), 31 had ICD. Patients with ICDs were 5.3 years younger (p=.01), used more frequently dopamine agonist (p=.02), alcohol (p=.009) and tobacco (p=.02). They were not more impulsive on BIS-11 (56 vs 58, p=.23, adjusted p=.46) and CE (p=.96). No relationship was found between dopaminergic medications and impulsivity or ICD severity. Among patients with ICD, impulsivity was correlated with ICD severity (BIS-11 r=.33, p=.001, adjusted p=.002, CE r=.53, p=.006). Multivariate regression analysis confirmed the independent predictive role of both measures. Conclusions: Impulsivity is not associated with increased prevalence of ICD in PD but it is strongly linked to ICD severity. When considering dopamine replacement therapy, assessment of impulsivity may be a useful approach to detect those patients at risk of severe forms of ICD.